A systematic review of disease prevalence, health-related quality of life, and economic outcomes associated with Friedreich's Ataxia. (3rd October 2022) - Buesch, Katharina; Zhang, Rongrong
Abstract: Introduction: Friedreich ataxia (FA) is a rare, inherited neuromuscular disease characterized by an early onset and progressive limb and gait ataxia. Currently, there are no approved treatments for FA. It is important to understand the burden of FA, including its extent and the most salient elements. The objective of this study is therefore to systematically review the literature regarding the aspects of prevalence, health-related quality of life (HRQoL), and economic outcomes that are associated with FA, and to subsequently identify relevant knowledge gaps. Methods: Three systematic literature reviews were conducted to assess publications regarding FA prevalence, HRQoL, and economic outcomes. Search strategies were implemented in MEDLINE (Ovid) and EMBASE databases; study selection and quality assessment were conducted using current best practices. For each review, study characteristics and findings were summarized. Results: A total of 36 studies were included. Review of prevalence studies ( n  = 22) indicated variation in the number of cases by region, and many regions were not represented at all. Regarding HRQoL ( n  = 12 studies), physical domains were consistently impacted, although findings regarding other domains and overall HRQoL were less clear. Cost studies ( n  = 2) encompassed 4 regions and revealed that costs related to the provision of care, including non-medical direct costs and indirect costs, accounted for the majority of FA-related costs. Discussion: Findings from this systematic review revealed several knowledge gaps that would preclude the conduct of a robust assessment of the benefits and outcomes associated with a disease-modifying FA therapy. Additional understanding regarding patient and caregiver HRQoL and costs is required.